(3GdCeGe GdMGaX LdGd GdOjf GdSjhWj (B:s (3hLghOg aj GdMOjK hYdheg (B/s - (3GddMGe, HOjY GdSjOs (Damascus : Dar Qutaybah, 1994)
Study of the contribution of al-Suyuti to the field of Hadith sciences.
Includes bibliographical references (p. 511-541) and indexes.
Keywords: Suyuti, -- 1445-1505 -- Contributions in Hadith studies; aHadith -- Study and teaching -- History